Transglutaminases in Dysbiosis As Potential Environmental Drivers of Autoimmunity - Lerner, Aaron; Aminov, Rustam; Matthias, Torsten (Frontiers in Microbiology, 2017)
Protein-glutamine γ-glutamyltransferases (transglutaminases, Tgs) belong to the class of transferases. They catalyze the formation of an isopeptide bond between the acyl group at the end of the side chain of protein- or peptide-bound glutamine residues and the first order 𝜀-amine groups of protein- or peptide-bound lysine. The Tgs are considered to be universal protein cross-linkers, and they play an essential role in a number of human diseases. In this review, we discuss mainly the bacterial Tgs in terms of the functionality of the enzymes and a potential role they may play in bacterial survival. Since microbial transglutaminases (mTgs) are functionally similar to the human homologs, they may be involved in the human disease provocation. We suggest here a potential involvement of Tgs in the pathologies such as autoimmune diseases. In this hypothesis, the endogenous mTgs that are secreted by the gut microbiota, especially in a dysbiotic configuration, are potential drivers of systemic autoimmunity, via the enzymatic posttranslational modification of peptides in the gut lumen. These mTg activities directed toward cross-linking of naïve proteins can potentially generate neo-epitopes that are not only immunogenic but may also activate some immune response cascades leading to the pathological autoimmune processes.